Pragmalinguistic experiment in literary translation (based on the translation of J. Rowling’s Harry Potter and the Philosopher’s Stone) - Beibitova А.С.; Konyratbayeva Ж.М.; Kapanova А.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
In contemporary research on literary translation, pragmalinguistic experiments focusing on the interaction between language and culture play a significant role. The article examines the importance of pragmalinguistic experiments in the process of translating literary texts. The main objective of our research is to identify the characteristics of pragmatic adaptation in translating literary works, taking into account linguistic and cultural specifics. The significance of conducting pragmalinguistic experiments in the field of literary translation lies in developing methodologies that account for pragmatic adaptation in translation practice. This methodology includes a comprehensive approach to text analysis based on the theories of pragmatics and linguistics. The main findings of the research indicate that literary translation requires not only linguistic accuracy but also the ability to convey the pragmatic meaning and intent of the author. The proposed results highlight the need for a deep understanding of cultural context and communicative norms to achieve a high level of equivalence in translation. The study broadens the understanding of the interaction between language and culture by integrating methods and approaches from translation studies and pragmalinguistics.